2012
DOI: 10.1111/j.1472-765x.2012.03239.x
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus aureus ST398 contamination and transmission in pigs after a low dose inoculation

Abstract: Summary Aims:  Methicillin‐resistant Staphylococcus aureus (MRSA) ST398 has recently been described as a zoonotic agent. Its transmission between animals seems to be a pivotal factor in its emergence and dissemination. This experimental trial was performed to describe MRSA ST398 contamination and transmission in pigs after a low dose inoculation. Methods and results:  Twelve specific pathogen‐free (SPF) pigs were randomly divided between two separate pens. Three pigs in each pen received a nasal inoculation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The exact extent to which the exposure of MRSA‐contaminated chicken meet contributes to the occurrence of human colonization, is also not included within the model. In pigs receiving nasal inoculation of bacteria, the lowest dosage for a successful MRSA colonization was 2 × 10 4 CFU (Jouy et al, ). In addition, Angen et al () showed that short‐term exposure to airborne MRSA poses a substantial risk for pig farms visitors to become nasal carriers, but the carriage is typically cleared within hours to a few days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact extent to which the exposure of MRSA‐contaminated chicken meet contributes to the occurrence of human colonization, is also not included within the model. In pigs receiving nasal inoculation of bacteria, the lowest dosage for a successful MRSA colonization was 2 × 10 4 CFU (Jouy et al, ). In addition, Angen et al () showed that short‐term exposure to airborne MRSA poses a substantial risk for pig farms visitors to become nasal carriers, but the carriage is typically cleared within hours to a few days.…”
Section: Discussionmentioning
confidence: 99%
“…The exact extent to which the exposure of MRSA-contaminated chicken meet contributes to the occurrence of human colonization, is also not included within the model. In pigs receiving nasal inoculation of bacteria, the lowest dosage for a successful MRSA colonization was 2 × 10 4 CFU (Jouy et al, 2012). In addition, Angen et al…”
Section: Model Outputmentioning
confidence: 99%
“…However, all studies used more or less artificial methods for MRSA exposure. Most of them utilized nasal drop-in only ( Broens et al, 2012 ; Jouy et al, 2012 ; Szabó et al, 2012 ; Verstappen et al, 2014 ) or the combination with skin ( Crombé et al, 2012 ) or gastrointestinal ( Moodley et al, 2011 ) inoculation. The dosage used here was between 10 7 cfu/mL ( Verstappen et al, 2014 ) and 10 8 cfu/mL ( Moodley et al, 2011 ; Broens et al, 2012 ; Crombé et al, 2012 ; Szabó et al, 2012 ), whereas this dosage did not always result in a successful colonization ( Moodley et al, 2011 ; Broens et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…At present, a number of experimental colonization models have been developed in order to understand colonization and transmission dynamics of LA-MRSA among pigs, with the aim of future use for development of intervention strategies (Table 2) (Moodley et al, 2011b; Broens et al, 2012a; Crombé et al, 2012b; Jouy et al, 2012; Szabó et al, 2012). The experimental design (i.e., inoculation strategy, type and dose of inoculum, age of the animals, strain, and use of antibiotics), the laboratory techniques as well as the pre-defined criteria for colonization of these models differ largely which makes comparison difficult.…”
Section: Pig Models To Study Colonization and Transmission Dynamicsmentioning
confidence: 99%
“…In contrast, Szabó et al (2012) reported colonization without any clinical implications though MRSA was detected in the inner organs (i.e., palatine tonsils, mandibular lymph nodes, spleen, lung, and ileocecal lymph nodes), 21 days after inoculation (Szabó et al, 2012). Interestingly in this context is that even if a low bacterial inoculum dose does not result in effective colonization, MRSA can be detected in the tonsils and the lymph nodes draining the neck (i.e., axillary, retropharyngeal, and cervical lymph nodes) (Jouy et al, 2012). It remains however unclear why high inoculum doses are needed to get individual animals colonized.…”
Section: Pig Models To Study Colonization and Transmission Dynamicsmentioning
confidence: 99%